2000
DOI: 10.1124/mol.58.3.601
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Gastrin-Releasing Peptide and Its Receptor Aberrantly Expressed by Human Colon Cancer Cell Lines

Abstract: Gastrin-releasing peptide (GRP) is a mitogen and morphogen important in the development of human colon cancers. Although epithelial cells lining the colon do not normally express GRP or its receptor (GRP-R), most human tumors express GRP-R mRNA. Yet functional protein has only been detected in 24 to 40% of colon cancers. To elucidate the reason for the difference between the expression of GRP/GRP-R mRNA and protein, we studied nine human colon cancer cell lines. Quantitative polymerase chain reaction revealed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 18 publications
2
23
0
Order By: Relevance
“…To test whether BBS induced an increase in [Ca 2 þ ] i , Caco-2 cells were loaded with the Ca 2 þ indicator dye Fura-2/AM and stimulated with BBS (100 nM) in the presence or absence of the BBS antagonist RC-3940-II. BBS elicited a rapid increase in [Ca 2 þ ] i , which was blocked by pretreating the cells with RC-3940-II (10 nM) (Figure 2a), confirming the expression of functional BBS/GRP-R on these cells (Carroll et al, 2000). This augmentation in [Ca 2 þ ] i could mediate activation of Cn, thus leading to NFAT activation and subsequently to Cox-2 induction.…”
Section: Resultsmentioning
confidence: 54%
See 2 more Smart Citations
“…To test whether BBS induced an increase in [Ca 2 þ ] i , Caco-2 cells were loaded with the Ca 2 þ indicator dye Fura-2/AM and stimulated with BBS (100 nM) in the presence or absence of the BBS antagonist RC-3940-II. BBS elicited a rapid increase in [Ca 2 þ ] i , which was blocked by pretreating the cells with RC-3940-II (10 nM) (Figure 2a), confirming the expression of functional BBS/GRP-R on these cells (Carroll et al, 2000). This augmentation in [Ca 2 þ ] i could mediate activation of Cn, thus leading to NFAT activation and subsequently to Cox-2 induction.…”
Section: Resultsmentioning
confidence: 54%
“…Aberrant expression of Cox-2, BBS/GRP and GRP-R has been observed in a variety of tumors, including colorectal carcinomas (Preston et al, 1995;Carroll et al, 1999Carroll et al, , 2000Gupta and Dubois, 2001;Jensen et al, 2001) and several lines of evidence suggest a link among these proteins in cancer progression (Hecht et al, 1997;Guo et al, 2001;Iishi et al, 2003). We have analysed the potential association between BBS-mediated signaling and Cox-2 in colon carcinoma cells, demonstrating that BBS stimulation of Caco-2 cells leads to a rapid upregulation of Cox-2 expression at both mRNA and protein levels resulting in increased production of PGE 2 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This analysis (Baldwin et al, 2007) demonstrated the sequence GVS-VFTLTALS (125-136 in murine BB 2 receptor) in the cytoplasmic side of TM3 is unique to the bombesin receptor family and is retained by all members; the cysteines residues in positions C94, C114, C197, C277, and C317 in the murine BB 2 are highly conserved in all BB 2 receptors, and the important amino acids described for determining GRP affinity are generally well conserved in all BB 2 receptors. BB 2 receptor mutations are reported to occur in human colon and gastric cancer and a number of these have identified and characterized (Carroll et al, 1999a(Carroll et al, , 2000bGlover et al, 2003 (Fig. 4) are found in colon and/or gastric cancers (Carroll et al, 1999a(Carroll et al, , 2000bGlover et al, 2003), and each resulted in no ligand binding of the expressed BB 2 receptor, demonstrating that these amino acids in the BB 2 receptor are essential for either receptor expression and/or binding.…”
mentioning
confidence: 99%
“…These receptors have been found in different tumor types. In particular, GRP receptors have been demonstrated in major human tumors such as breast cancer (70%) and prostate cancer (30 of 30 invasive prostatic cancers) and in highdensity prostatic intraepithelial lesions, peritumoral vessels of ovarian cancer, renal cell cancer, small cell lung cancer, and gastrointestinal stromal tumors (70)(71)(72)(73)(74)(75).…”
Section: Radiolabeled Bombesin/gastrin-releasing Peptide (Grp) Analogsmentioning
confidence: 99%